Performance Analysis of Hybrid Passive Optical Networks - Rakesh (My University, 2015)
The rapid augmentation in the access networks demands huge bandwidth to provide voice, data and video (triple play) services for residential and corporate subscribers. Due to the higher bandwidth requirement, optical broadband access networks are the most promising solution for the demand of high channel capacity at longer transmission distance. The researchers are giving more focus on the designing and implementation of innovative access system architecture, sustaining huge data at high speed with larger bandwidth for the next generation demands. Passive Optical Networks (PONs) appealed to provide a lucrative, highly flexible and scalable network for all the end subscribers. One aspect of achieving higher data rates over fiber to fulfill the large bandwidth demand is multiplexing techniques. On the basis of multiplexing techniques, PONs can be divided into two main schemes viz. Wavelength Division Multiplexing (WDM) and Time Division Multiplexing (TDM) schemes. In recent times, researchers are aiming at the concepts of hybrid (WDM/ TDM) PON. This thesis deals with the performance evaluation of hybrid PON systems by designing new architectures, finding out suitable amplifier, improving the overall performance by mitigating & analyzing the crosstalk and implementing different topologies with tracking several system level challenges while acknowledging the limitations of existing networks. In order to achieve these objectives, it is utmost important to design, characterize and investigate hybrid PON for high capacity access systems. Firstly, we have proposed various architectures of hybrid PONs and analyzed the performance and feasibility of these architectures. In the first architecture, a hybrid PON using triple play services is simulated for 128 Optical Network Units (ONUs) for suitability of various data formats. Further, a bidirectional hybrid PON using circulator has been investigated for different data rates i.e. 1.25, 2.5, 5 and 10 Gbps. The next architecture is designed for Mixed Line Rates (MLRs) for 10/ 20/ 40 Gb/s to meet the requirement of high volume of heterogenic traffic. The investigation is focused on uniform channel spacing and mixed channel spacing for MLRs. 50 GHz spacing is kept in case of uniform spacing and 20, 50 & 100 GHz spacing for 10, 20 & 40 Gbps data rates is given in case of mixed spacing respectively. It is found that mixed channel spacing for MLRs shows better results than conventional uniform channel spacing. Further, the network is constructed based on a novel technique i.e. cost effective using common carrier for all optical network units technique. A carrier is engendered at the central office (CO) and remodulated for upstream transmission at the subscriber end making ONU very simple and cost effective. So, there is no requirement of laser sources for generation of carrier at the ONU end. In this way, by using the extra carrier at Optical Line Terminal (OLT), we have reduced the laser sources equal to the number of ONUs. Further, we have proposed different aggressive schemes to reduce the energy consumption viz. no buffer, with buffer, reduced buffer and reduced buffer with small packet. The reduced buffer with small packet scheme has shown a reduction of more than 35% of total leakage power at the central office with the compromise of delay in packets receiving. Bidirectional hybrid PONs for Raman, Semiconductor Optical Amplifier (SOA) and Erbium Doped Fiber Amplifiers (EDFA) using polarization modulation technique in swing with Quadrature Amplitude Modulation (QAM) at 5 Gbps data rate has also been proposed. Further, the system is enhanced to 10 Gbps data rate with 128 ONUs using polarization modulation with 16-QAM to utilize the maximum bandwidth. It has been observed that EDFA amplifier shows better performance than SOA and Raman. Then, a bidirectional hybrid PON for the various fiber nonlinearities like Stimulated Brillouin Scattering (SBS), Stimulated Raman Scattering (SRS), Four Wave Mixing (FWM) and Cross Phase Modulation (XPM) is analyzed theoretically. The proposed system is very simple, flexible, expandable and cost effective. All kind of distortions at the same frequency, phase and power are included into the same signal. The resultant signal is sent to a threshold device where a threshold level is defined on the basis of the centre frequency of these distortions. The output of the threshold device is free from distortions. Different wavelengths for downstream and upstream i.e. 1550 nm and 1300 nm are also used to mitigate the crosstalk effect of same wavelength in the fiber respectively. Further, we have investigated the network for 1024 number of users with hybrid (ring-tree) topology form using Add Drop Multiplexers. A cost effective fault protection scheme is also proposed for hybrid passive optical network using ring topology. This scheme provides the full fault protection to PON without installing the extra standby fiber in the ring network. Therefore, this investigation establishes to design, characterize and investigate hybrid PON as high capacity access systems resulting in the revolutionary growth of internet traffic for terrestrial fiber backbone networks.
Ph.D (ECED)
Keywords: Hybrid Passive Optical Networks; Crosstalk; CCAONU; WDM/ TDM; EDFA; SOA